2019
DOI: 10.7150/thno.37574
|View full text |Cite
|
Sign up to set email alerts
|

STING activation in cancer immunotherapy

Abstract: Cancer immunotherapy modulates and leverages the host immune system to treat cancer. The past decade has witnessed historical advancement of cancer immunotherapy. A myriad of approaches have been explored to elicit or augment anticancer innate immunity and/or adaptive immunity. Recently, activation of stimulator of interferon (IFN) genes (STING), an intracellular receptor residing in the endoplasmic reticulum, has shown great potential to enhance antitumor immunity through the induction of a variety of pro-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 93 publications
1
128
0
Order By: Relevance
“…Over the past few years, these observations prompted an intense wave of investigation aimed at the identification and development of pharmacological STING agonists for use in cancer patients. 9,68,91,92 Historically, flavone acetic acid (FAA) has been the first of such molecules to be investigated for its anticancer properties, although FAA was not known to trigger STING activation at that time. 93 Indeed, FAA was originally characterized as a vascular-disrupting agent that showed some antitumoral activity against murine colon tumors.…”
Section: Sting Signaling In Preclinical Tumor Modelsmentioning
confidence: 99%
“…Over the past few years, these observations prompted an intense wave of investigation aimed at the identification and development of pharmacological STING agonists for use in cancer patients. 9,68,91,92 Historically, flavone acetic acid (FAA) has been the first of such molecules to be investigated for its anticancer properties, although FAA was not known to trigger STING activation at that time. 93 Indeed, FAA was originally characterized as a vascular-disrupting agent that showed some antitumoral activity against murine colon tumors.…”
Section: Sting Signaling In Preclinical Tumor Modelsmentioning
confidence: 99%
“…Recently studies demonstrated that STING pathway had tremendous potential for immunotherapy from bench to bedside (24,(45)(46)(47). However, whether STING pathway involved in neuropathic pain process and whether STING pathway regulate ER-phagy process still remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al synthesised a 2′3′-cGAMP analogue, 2′3′-cG S A S MP, which was resistant to ENPP1 hydrolysis and showed similar affinity for hSTING in vitro as well as ten-fold more potent induction of IFN-β secretion from THP-1 cells. This bisphosphothioate analogue was also ~40 times more resistant to ENPP1 hydrolysis than the naturally occurring ligand, rendering it a desirable compound for future development [ 15 , 79 ]. Gajewski et al synthesised various synthetic CDN-derivatives and selected those which displayed binding affinity for all hSTING alleles while retaining the ability to bind mSTING [ 20 ].…”
Section: Sting Activating Drugsmentioning
confidence: 99%